Causal association of gut microbiota on spondyloarthritis and its subtypes: a Mendelian randomization analysis - Tang, Jun; Mo, Shiyan; Fan, Lina; Fu, Shihui; Liu, Xiaofei (Frontiers in Immunology, 2024)
Background Despite establishing an association between gut microbiota and spondyloarthritis (SpA) subtypes, the causal relationship between them remains unclear. Methods Gut microbiota data were obtained from the MiBioGen collaboration, and SpA genome-wide association study (GWAS) summary data were obtained from the FinnGen collaboration. We conducted a two-sample Mendelian randomization (MR) analysis using the inverse-variance-weighted method supplemented with four additional MR methods (MR-Egger, weighted median, simple mode, and weighted mode). Pleiotropy and heterogeneity were also assessed. Reverse MR analysis was used to detect reverse causal relationships. Results We identified 23 causal links between specific gut microbiota taxa and SpA levels. Of these, 22 displayed nominal causal associations, and only one demonstrated a robust causal connection. Actinobacteria id.419 increased the risk of ankylosing spondylitis (AS) (odds ratio (OR) = 1.86 (95% confidence interval (CI): 1.29–2.69); p = 8.63E−04). The family Rikenellaceae id.967 was associated with a reduced risk of both AS (OR = 0.66 (95% CI: 0.47–0.93); p = 1.81E−02) and psoriatic arthritis (OR = 0.70 (95% CI: 0.50–0.97); p = 3.00E−02). Bacillales id.1674 increased the risk of AS (OR = 1.23 (95% CI: 1.00–1.51); p = 4.94E−02) and decreased the risk of enteropathic arthritis (OR = 0.56 (95% CI: 0.35–0.88); p = 1.14E−02). Directional pleiotropy, or heterogeneity, was not observed. No reverse causal associations were observed between the diseases and the gut microbiota. Conclusion Our MR analysis suggested a genetic-level causal relationship between specific gut microbiota and SpA, providing insights into the underlying mechanisms behind SpA development mediated by gut microbiota.